Service Quality Analysis Of Tokopedia And Shopee Mobile Commerce Applications Using Mobile Service Quality (M-S-QUAL) And Importance Performance Analysis (IPA) Methods - Kamila, Khairunnisa Ayudia; Muhammad, Katon; Asyari, Hasyim (Department of Industrial Engineering, Universitas Jenderal Soedirman., 2023)
The increasingly rapid development of technology has led to the emergence of mobile commerce (m-commerce) as a new business phenomenon. Tokopedia and Shopee are m-commerce that are widely used by Indonesian people compared to other m-commerce. However, the Tokopedia and Shopee applications still have problems such as crashes, errors, buffering, bugs, an unfriendly and messy UI display, search features that are not suitable or working properly, unhelpful customer service, and other user complaints felt by users towards service quality. The existence of these complaints can create a gap between the services provided by the application and the services expected by users. Therefore, this research was conducted to determine the quality of service on the Tokopedia and Shopee applications by measuring service quality using the M-S-QUAL method and identifying priority service attributes that require improvement using the Importance-Performance Analysis (IPA) method. Research data was obtained from the results of questionnaires to 100 respondents who used Tokopedia and Shopee. Based on the calculation results, the Tokopedia and Shopee applications have a negative average gap value in all dimensions, meaning that the service quality of the Tokopedia and Shopee applications has not met the expectations of their users. Then, the results of the analysis using Importance Performance Analysis (IPA) obtained 8 attributes on Tokopedia (EF2, EF3, EF5, EF7, EF8, SA3, SA4, and CON3) and 8 attributes on Shopee (EF5, EF7, EF8, SA3, SA4, COM3, CON2, and CON3) which are the main priorities for improvement. Thus, these attributes will be given recommendations for improvement to increase or improve the quality of the service.